PENERAPAN NILAI-NILAI MODERASI BERAGAMA DALAM PEMBELAJARAN FIQIH DI PTKIS MENGGUNAKAN KONSEP PROBLEM-BASED LEARNING - Ibnu Mas’ud (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2023)
Moderate values ??or wasathiyah are important to maintain as the collective consciousness of Muslims in Indonesia. This is because it will later become a bond of politeness in dealing with diversity within the Muslim body itself as well as the diversity of other parties. PTKIS as an educational institution as well as an institution under the auspices of the Ministry of Religion must contribute to spreading the value of moderation to its students through learning. Fiqh learning can be a forum for instilling the value of religious moderation by presenting the concept of problem-based learning which requires students to broaden their horizons widely and openly regarding the differences in Islamic law applied in society so that they are able to position themselves to be in the middle and act moderately in responding to the differences that arise. There is. By instilling moderate values, it is hoped that PTKIS can prepare Indonesian citizens who are Muslim while maintaining the values ??of wisdom, tolerance and not being radical